Portuguese Neology ‘Didactization’ - Cambuta, José (Linha D’Água, 2019)
This article is the synthesis of a long-way research which has crowned with the doctoral thesis which reflects upon the Portuguese language neology in Angola. Since Angola is a multilingual and multicultural country, this research is circumscribed to Umbundu Linguistic Zone (ULZ), to Angola Centre-Southern. The research was especially about the Portuguese linguistic behavior in contact with Umbundu Language for checking the teaching need of Portuguese lexical and neology. The aim of this study is to reflect on the phenomenon of neology and, in particular, on its didactics in school contexts.